Judging school discipline : the crisis of moral authority - Arum, Richard (Harvard University Press, 2003)
Annotation Reprimand a class comic, restrain a bully, dismiss a student for brazen attire--and you may be facing a lawsuit, costly regardless of the result. This reality for today's teachers and administrators has made the issue of school discipline more difficult than ever before--and public education thus more precarious. This is the troubling message delivered in Judging School Discipline, a powerfully reasoned account of how decades of mostly well-intended litigation have eroded the moral authority of teachers and principals and degraded the quality of American education. Judging School Discipline casts a backward glance at the roots of this dilemma to show how a laudable concern for civil liberties forty years ago has resulted in oppressive abnegation of adult responsibility now. In a rigorous analysis enriched by vivid descriptions of individual cases, the book explores 1,200 cases in which a school's right to control students was contested. Richard Arum and his colleagues also examine several decades of data on schools to show striking and widespread relationships among court leanings, disciplinary practices, and student outcomes; they argue that the threat of lawsuits restrains teachers and administrators from taking control of disorderly and even dangerous situations in ways the public would support.